Evaluation of Direct Immunofluorescence Assay and Cytological Examination in Comparison to Polymerase Chain Reaction of Conjunctival Swabs in Patients with Adult Inclusion Conjunctivitis. (July 2013) - Malamos, Panagiotis; Georgalas, Ilias; Rallis, Konstantinos; Andrianopoulos, Konstantinos; Konstantoulakis, Panteleimon; Georgopoulos, Gerasimos; Theodosiadis, Panagiotis; Markomichelakis, Nikos N.
Abstract Purpose: To evaluate PCR, direct immunofluorescence assay (DIA) and cytological test of conjunctival swabs for the diagnosis of adult follicular conjunctivitis (AFC). Methods: Eighty-three adult patients with chronic conjunctivitis and sixteen healthy individuals were included. Conjunctival scrapings underwent PCR, DIA and cytological analysis. Exams were repeated two weeks after treatment application. Sensitivity, specificity and agreement rate with PCR of DIA and Cytology were evaluated and correlated with clinical symptoms/signs. Results: Cytology test was more sensitive than DIA and presented an acceptable agreement with PCR (K = 0.44) in treatment-na patients, concerning especially the combination of both conventional exams (K = 0.77). Inferior diagnostic performance of was detected post-treatment, considering the combination as well (K = 0.40). Negative post-treatment PCR correlated well with significant relief of symptoms/signs. Conclusion: Combination of Cytology and DIA seems to be a useful diagnostic option for treatment na AFC patients. However, PCR remains the most reliable test for post-treatment evaluation.